Tooth brushing time table media as an effort to increase the independence of brushing teeth in preschool children - Fatimah, Neny; Widiyastuti, Rini (Journal Center of Excellent : Health Assistive Technology, 2024)
Background: Based on the Basic Health Research in 2018, in Banten province, the population who have dental problems in the form of damaged teeth, cavities or pain in the 3 - 4 year old group with a percentage of 36.4% and the 3 - 4 year old group who do tooth brushing care with the correct time is only 1.1%. Therefore, it is necessary to provide dental health education to children using methods and learning media that are tailored to child development. One of the methods used is by monitoring toothbrushing using toothbrush time table media.  Objective: analyzing toothbrush time table media as an effort to increase the independence of brushing teeth in preschool children Methods: This study used a quasi experiment with pretest and post test design, conducted on 77 students as respondents obtained using the total sampling technique. The type of data used is primary data, which is data obtained directly by measuring the level of children's tooth brushing independence. The instrument used was a tooth brushing independence checklist sheet. Results: The results of the study before and after using the toothbrush time table media on 77 respondents, with the category needing guidance as many as 64 students (83.1%), became excellent toothbrushing independence as many as 60 students (77.9%), and the mean of toothbrushing independence with the results of 47.9, namely the category needing guidance changed to 87.9 with an excellent category, with independence p-value of 0.001 (p <0.05). Conclusion: The tooth brushing time table media can increase the independence of tooth brushing in preschool children